A new spatial angle assembly method of the ICF target. (3rd May 2017) - Wu, Wenrong; Bi, Lie; Du, Kai; Zhang, Juan; Yang, Honggang; Wang, Honglian
Abstract : The designs of inertial confinement fusion (ICF) targets, which field on ShenGuang III, are becoming more complex and more stringent in terms of assembly precision. A key specification of these targets is the spatial angle alignment accuracy. To meet these needs, we present a new spatial angle assembly method, using target part's 3D model-based dual orthogonal camera vision, which is better suited for the flexible automation of target assembly processes. The two-hands structure micromanipulate system and dual orthogonal structure visual feedback system were investigated by considering the kinematics, spatial angle measuring, and motion control in an integrated way. In this paper, we discuss the measurement accuracy of spatial angle assembly method, which compared the real-time image acquisition with the redrawing 2D projection. The result shows that the assembly method proposed is very effective and meets the requirements of angle assembly accuracy, which is less than 1^° . Also, this work is expected to contribute greatly to the advancement of other target microassembly equipments.